الحال المفردة في سورة آل عمران تحليلها وتر تها إلى الملايوية: تر ان المستفيد لشيخ عبد الرؤوف بن علي الفنصوري ) 1615 م- 1693 م( نموذجا - Wan Moharani Mohammad; Nurhasma Muhamad Saad; Zulkipli Md. Isa; Farah Nadia Harun; Muhammad Marwan Ismail; Sulaiman Ismail (Penerbit USIM, 2025)
International Conference of Quran as Foundation of Civilization (SWAT 2025) : Maqasid al-Quran and the Madani Vision: A Guiding Light for Regional Serenity and Global Unity Organized by : Faculty of Quranic and Sunnah Studies, in collaboration with Nasyrul Quran and Daffodil International University, Bangladesh. Date:12-13 November 2025